Experience with large fiscal adjustments - Tsibouris, George C.; International Monetary Fund. (Washington, DC : International Monetary Fund, 2006)
"This Occasional Paper analyzes the experience of countries that have implemented very sizable fiscal adjustments over the past three decades. It aims to identify key conditions and institutional approaches that have contributed to sustained outcomes and to favorable macroeconomic developments. In this way, the paper may provide operational guidance to policymakers" -- pref.
Includes bibliographical references (p. 44).
Keywords: Fiscal policy; Structural adjustment (Economic policy)